Representações do trabalho docente de professores de língua portuguesa em formação - Lima, Wendel dos Santos (2014)
This research discusses the teaching work in the perspective of Socio- Discursive Interactionism - SDI - (Bronckart, 2009) and analyzes the representations of the educational activity of graduating students of Letras at a public university in the state of RS. The theoretical framework is based on the SDI in particular in shed that discusses the work of teachers (Bronckart; MACHADO, 2004; 2009). The methodology follows the assumptions of analysis of SDI (Bronckart 1999, 2006, 2008 , AXE, 2004, 2009; AX; Bronckart, 2004, 2009) examines excerpts from a corpus whose source texts are produced by six academics, in an interview situation, ar 8th semester of the course. The analysis and discussion of results focus on the thematic content of these texts in relation to choice of course, the "desire" to be teacher, "to be a teacher" and teaching as work. The results indicate that entering graduate degree in Letras came not with the intention of becoming a teacher of Portuguese Language and / or Literature and in relation to "be a teacher", the representation that stands out most is the one that places the teacher as the agent of the teaching / learning and the representations presented as educational work process also appear quite limited.